Designing an effective climate-policy mix: accounting for instrument synergy. (3rd July 2021) - van den Bergh, J.; Castro, J.; Drews, S.; Exadaktylos, F.; Foramitti, J.; Klein, F.; Konc, T.; Savin, I.
ABSTRACT: We assess evidence from theoretical-modelling, empirical and experimental studies on how interactions between instruments of climate policy affect overall emissions reduction. Such interactions take the form of negative, zero or positive synergistic effects. The considered instruments comprise performance and technical standards, carbon pricing, adoption subsidies, innovation support, and information provision. Based on the findings, we formulate climate-policy packages that avoid negative and employ positive synergies, and compare their strengths and weaknesses on other criteria. We note that the international context of climate policy has been neglected in assessments of policy mixes, and argue that transparency and harmonization of national policies may be key to a politically feasible path to meet global emission targets. This suggests limiting the complexity of climate-policy packages. Key policy insights Combining technical standards or targets, such as renewable-energy quota, or adoption subsidies with a carbon market can produce negative synergy, up to the point of adding no emissions reduction beyond the cap. For maximum emissions reduction, renewable energy policy should be combined with carbon taxation and target expensive reduction options not triggered by the tax. Evidence regarding synergy of information provision with pricing is mixed, indicating a tendency for complementary roles (zero synergy). Positive synergy is documented only for cases where information provision improves effectiveness of price instruments, e.g. by stimulating social imitation of low-carbon choices. We conclude that the most promising packages are combining innovation support and information provision with either a carbon tax and adoption subsidy, or with a carbon market. We further argue that the latter could have stronger potential to harmonize international policy, which would allow to strengthen mitigation policy over time.